ANATOMIALAT PENCERNAAN IKAN BUNTAL PISANG (Tetraodon lunaris) [Anatomy of The Digestive Apparatus of The Puffer Fish Tetraodon lunaris] - Yusfiati Yusfiati; Koeswinarning Sigit; Ridwan Affandi; Nurhidayat Nurhidayat (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2006)
This research was aimed to study not only on gross morphologically but also on the histological structure of the Tetraodon lunaris digestive apparatus. The fish samples were obtained from a fisherman at the fish auction in Pelabuhan Ratu, from August 2005 until March 2006. The ratio between intestine and length/body length represented that this fish is carnivorous. The esophagus is short and the gastric forms a simple pouch with two of small diverticula. The intestine consists of a single loop. The esophagus and gastric mucous layer is covered with epithelial stratified cells. The intestine mucous layer has covered with a layer of columnar epithelial cells. The esophagus and gastric muscular layer consist of striated muscle. The sphincter pylorica and the intestine muscular layer consist of smooth muscle. The anus mucous layer consits of epithelial cuboid and it has the muscular layer of striated muscles. The liver has oval-shaped greenish vesica fellea with ductus choledochus emptied at the anterior part of intestine. The hepatocyt cells have a polygonal shape with lipid droplets in its. The exocrine glands of the pancreas tissue showed a set of acinar cells in the liver parencyhm, around portal vein, hepatic artery and biliary ductules.